Online Media Archeology as AI Critique: Wikipedia’s Links and Edits as Spatial and Temporal Fields - Stanusch, Natalia Barabra; Rogers, Richard; Sánchez-Querubín, Natalia (AoIR Selected Papers of Internet Research, 2026)
There have been many impulses to make sense of artificial intelligence, or what AI ‘is.’ We propose that media archeology on Wikipedia can aid in the sensemaking of AI. Wikipedia’s technicity - its linked article ecology together with its edit histories - makes it suitable to perform a media archeology, which already favors spaciousness and complexities. The starting point for the analysis is the ‘Artificial intelligence’ article on Wikipedia. We then operationalize the ‘See also’ section into a link ecology with categorizations and prominence over time, thus allowing us to map and explore the spatial field within which the artificial intelligence article has resided across its temporal dimension. This means approaching Wikipedia as a source of data about not only content but also the connections and ruptures. By ‘ruptures’ we mean changes by deletion or substitution in article associations. Ultimately, taking inspiration from media archeology’s presumption to unearth understandings of media technologies through their multiple dimensions and ruptures, we present our findings in terms of the ‘ideation company’ that AI keeps on Wikipedia. First, we notice the instability of the AI industry. Second, we observe a decline in the prominence of science fiction-related articles over time. The rise of articles under the umbrella of human enhancements can be seen in the most recent periods, as well as the rising prominence of articles related to threat recognition and accountability of AI. In our investigation, Wikipedia emerges as a (substantive) AI sense-making space as well as a media archeology instrument.